PENGARUH KEMAMPUAN PEMIMPIN KEPALA DESA TERHADAP PENERAPAN GOOD VILLAGE GOVERNANCE DI DESA JEBLOGAN, KECAMATAN PARON, KABUPATEN NGAWI - Haryonno, Hafids; Ma'ruf, Muhammad Farid (Universitas Negeri Surabaya, 2023)
This study aims to investigate the influence of the leadership skills of the Jeblogan Village Head on the implementation of Good Village Governance. This research uses a quantitative approach by collecting data through questionnaires distributed to the people of Jeblogan Village. The probability sample method was used to select research samples based on predetermined criteria with 115 respondents involved. The results of data analysis show that the coefficient path between the leader ability constructs produces a t-statistic value of 19.227 and a p-value of 0.000, with the test criteria that with an alpha value (a) = 5%, the coefficient path is declared significant if the t-statistic value is more than 1.96 and the p-value is less than 0.05. Thus, the ability of the leader of the Jeblogan Village Head has a positive and significant influence on the implementation of Good Village Governance. This indicates that the higher the leader's ability to lead and manage the village, the better the implementation of good governance principles in Jeblogan Village. These findings have important implications for village development in Indonesia. Greater attention needs to be given to the development of leadership skills for the Jeblogan Village Head and other village leaders, so that they can be effective in implementing Good Village Governance. In addition, stakeholders, both government and community, also need to support and actively participate in efforts to improve the implementation of good governance principles at the village level. Penelitian ini bertujuan untuk menginvestigasi pengaruh kemampuan pemimpin Kepala Desa Jeblogan terhadap penerapan Good Village Governance. Penelitian ini menggunakan pendekatan kuantitatif dengan pengumpulkan data melalui kuesioner yang dibagikan kepada masyarakat Desa Jeblogan. Metode sampel probabilitas digunakan untuk memilih sampel penelitian berdasarkan kriteria yang telah ditetapkan dengan responden yang terlibat sebanyak 115. Hasil analisis data menunjukkan bahwa jalur koefisien antara konstruk kemampuan pemimpin menghasilkan nilai t-statistik sebesar 19,227 dan nilai p-value sebesar 0,000, dengan kriteria pengujian bahwa dengan nilai alpha (a) = 5%, jalur koefisien dinyatakan signifikan jika nilai t-statistic lebih dari 1,96 dan nilai p-value kurang dari 0,05. Sehingga, kemampuan pemimpin Kepala Desa Jeblogan memiliki pengaruh positif dan signifikan terhadap penerapan Good Village Governance. Hal ini menunjukkan bahwa semakin tinggi kemampuan pemimpin dalam memimpin dan mengelola desa, semakin baik penerapan prinsip-prinsip tata kelola yang baik di Desa Jeblogan. Temuan ini memiliki implikasi penting bagi pengembangan desa di Indonesia. Diperlukan perhatian yang lebih besar terhadap pengembangan kemampuan kepemimpinan bagi Kepala Desa Jeblogan dan pemimpin desa lainnya, agar mereka dapat efektif dalam menerapkan Good Village Governance. Selain itu, para pemangku kepentingan, baik pemerintah maupun masyarakat, juga perlu mendukung dan berpartisipasi aktif dalam upaya meningkatkan penerapan prinsip-prinsip tata kelola yang baik di tingkat desa.